Xanthohumol Inhibits the Growth of Keratin 18-Overexpressed Esophageal Squamous Cell Carcinoma in vitro and in vivo - Yin, Shuying; Song, Mengqiu; Zhao, Ran; Liu, Xuejiao; Kang, Woo Kyu; Lee, Jeong Min; Kim, Young Eun; Zhang, Chengjuan; Shim, Jung-Hyun; Liu, Kangdong; Dong, Zigang; Lee, Mee-Hyun (Frontiers in Cell and Developmental Biology, 2020)
Esophageal squamous cell carcinoma (ESCC) is a leading cause of cancer-related death worldwide. Xanthohumol is a prenylated flavonoid isolated from hops. Although xanthohumol has been reported to exert anti-obesity, hypoglycemic, anti-hyperlipidemia and anti-cancer activities, the mechanisms underlying its chemotherapeutic activity are yet to be elucidated. In the present study, we found that xanthohumol inhibited ESCC cell proliferation in vitro and in vivo by targeting keratin (KRT)-18. Xanthohumol suppressed the proliferation, foci formation and anchorage-independent colony growth of KYSE30 cells. Using xanthohumol-sepharose conjugated bead pull-down and mass/mass analysis, we found that KRT18 is a novel target of xanthohumol in KYSE30 cells. KRT18 protein was highly expressed in patient ESCC tissues compared to adjunct tissues. Anti-proliferative activity of xanthohumol was abrogated or enhanced according to the knockdown or overexpression of KRT18 protein, respectively. Xanthohumol also induced apoptosis and cell cycle arrest at G1 phase which was associated with the modulation of expression of related makers including cyclin D1, cyclin D3, and cleaved-PARP, Bcl-2, cytochrome c and Bax. While xanthohumol attenuated KRT18 protein expression, it failed to cause any change in the KRT18 mRNA level. Furthermore, oral administration of xanthohumol decreased tumor volume and weight in patient-derived xenografts (PDXs) tumors having overexpressed KRT18. Overall these results suggest that xanthohumol acts as a KRT18 regulator to suppress the growth of esophageal squamous cell carcinoma.